Low back pain in young team sport players: A retrospective study - Pasanen, K.; Rossi, M.; Heinonen, A.; Parkkari, J.; Kannus, P. (British Journal of Sports Medicine, 2014)
Background: Low back pain (LBP) is a common complaint in general population affecting both genders and almost all age-groups. LBP is a common problem in sports as well, even in younger populations. LBP is prone to recur, thus there is a need for studies on the early phases of the problem in different sports. Objective: To investigate the prevalence, nature, severity and risk factors of self-reported LBP in young team sport players. Design: A retrospective cross-sectional study. Setting: Finnish female and male basketball, floorball, ice hockey and volleyball teams. Participants:. This study is a part of an ongoing cohort study exploring risk factors for sports injuries. Players from 22 teams, a total of 464 young players (16±1.9 years), have been included. Risk factor assessment :Players' gender, age, sport and family LBP history were assessed as risk factors. Main outcome measurements: Prevalence of LBP provided by a standardized Nordic questionnaire. LBP was defined: ache, pain or discomfort of lumbar region with or without radiation to one or both legs. Results: 255 (54.9 %) of all players had suffered LBP during the previous year. 73 (15.7 %) had received medical attention for LBP. 51 players (11.0 %) had suffered over 4 weeks' total duration of pain symptoms during the previous year. 80 (17.2 %) reported missing training because of LBP. Male players had more time-loss from training due to LBP than females. Family history of LBP and higher age were associated with LBP in players. Conclusions: Low back pain is a relatively common complaint in young team sport players. Preventive measures are needed to reduce low back pain in youth sports.